Prey-Predator Type Biological Model of Four Species Interacting in a Natural Environment with a Holling I Type Functional - Dosso, Mouhamadou; Lagui, Thierry Bi Boua; Koné, Bakary (Journal of Applied Nonlinear Dynamics, 2026)
We propose a prey-predator type model with four interacting species. We carry out a mathematical analysis of the proposed model followed by a numerical analysis. We plan to examine the dynamics of different populations in an interaction where the super predator has a diverse food source. The mathematical analysis first concerns the existence, bounding and stability (local and global using the Routh-Hurwitz criterion and the Lyapunov principle) of the solutions. In addition, we look for conditions under which solutions persist or die out. Finally, numerical simulations are carried out to illustrate the theoretical results.